การแสดงออกของ แอนเน็กซิน เอ-วัน และ ยูซีเอช-แอลวัน ในเนื้องอก ระบบประสาทส่วนกลางที่มีต้นกำเนิดมาจากนิวโรเอพิธีเลี่ยม - กนกกาญจน์ ทาแก้ว (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
Background: Pathological diagnosis of CNS neuroepithelial tumors can be problematic due morphological similarity, and many tumors in the group also share immunohistochemical profile as they have common cellular origin. New immunohistochemical marker is needed to enhance diagnosis. Objective: To study Annexin A1 and UCH-L1 expression in CNS neuroepithelial tumors, with regard to a possible application of these markers for practical usage. Methods: Expression of Annexin A1 and UCH-L1 was evaluated in 223 various neuroepithelial tumors by immunohistochemistry using tissue microarray. Results: Annexin A1 was expressed by the majority of ependymoma (92%) but none of central neurocytoma (p = 0.0000002) and medulloblastoma (p < 10-8). UCH-L1 expression level was significantly higher in glioblastoma than in pilocytic astrocytoma (p=0.001). Absence of Annexin A1 and/or UCH-L1 was associated with low-grade astrocytoma rather than ependymoma (p = 0.0000009). Percentage of positive Annexin A1 and UCH-L1 paralleled increasing histologic grades in diffuse astrocytomas. Conclusion: Annexin A1, UCH-L1 and combined Annexin A1/UCH-L1 may be the additional markers that useful in the differential diagnosis of neuroepithelial tumors. Upregulation of Annexin A1 and UCH-L1 in increasing histologic grade of diffuse astrocytomas suggests their roles in the malignant transformation.